Compact modeling of nanoscale triple-gate junctionless transistors covering drift-diffusion to quasi-ballistic carrier transport. (April 2018) - Oproglidis, T.A.; Karatsori, T.A.; Barraud, S.; Ghibaudo, G.; Dimitriadis, C.A.
Highlights: The drift-diffusion compact model for JLTs is extended to quasi-ballistic regime. The model is based on reformulation of the low-field mobility. Effect of non-ideal drain contact on the threshold voltage and ideality factor. Validation of the model for transistors with channel length down to 25 nm. Abstract: In this work, we extend our analytical compact model for nanoscale junctionless triple-gate (JL TG) MOSFETs, capturing carrier transport from drift-diffusion to quasi-ballistic regime. This is based on a simple formulation of the low-field mobility extracted from experimental data using the Y-function method, taking into account the ballistic carrier motion and an increased carrier scattering in process-induced defects near the source/drain regions. The case of a Schottky junction in non-ideal ohmic contact at the drain side was also taken into account by modifying the threshold voltage and ideality factor of the JL transistor. The model is validated with experimental data for n-channel JL TG MOSFETs with channel length varying from 95 down to 25 nm. It can be easily implemented as a compact model for use in Spice circuit simulators.